STUDY OF BREATH OF ADOLESCENTS WITH CHRONIC DYSPEPSIA BY MEANS OF NEW GAS-SENSITIVE SENSORS: METHODIC ASPECTS - Kusch, I.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
New gas-sensitive sensors based on synthetic organic conductors were applied to clinical practice for the first time to analyze human breath gas. Methodic of breath test of adolescents suffered from chronic dyspepsia was developed and adapted for pediatrics. Sensor responses upon breath of ill patients were studied under different duration of exposition. It was revealed that response curve transforms to more complex dependence under prolong exposition of gas-sensitive material in breath environmental: new peculiarities appear. Characteristic parameters of such response curve were determined. They provide computer analysis of obtained data. Proposed approach is a basis for further development of a new noninvasive breath test for adolescents with chronic dyspepsia.